Hubungan Ketimpangan Pendapatan Terhadap Pertumbuhan Ekonomi - Fathoni, Muhammad (Journal of Student Development Informatics Management (JoSDIM), 2023)
Problems such as inequality and economic inequality are two big problems that are often experienced by developing countries, with the inequality of income distribution between high- income groups and low-income groups. High economic growth at the development stage can indeed be achieved, but it is accompanied by problems such as unemployment. The method used in this research is the library research method. Recent studies show that the relationship between income inequality and economic growth through several channels (channels). The largest and smallest income inequality can affect the existing economic growth.